Towards Improving the Performance of Women Entrepreneurs in Micro Enterprise in Nigeria - Musa Hammawa, Yusuf; Bappi, Usman (Kashere Journal of Humanities, Management and Social Sciences, 2022)
This study was designed to explore women entrepreneur’s activities and related performance. It was also designed to examine the relationship between microfinance resource’s factors that include access to finance, savings, and women microenterprises performance in Nigeria. Data were collected from the women microenterprises operating in Gombe, Nigeria, using a cross-sectional study design. The study adopted stratified sampling technique. Three hundred and sixty-three usable data were gathered to determine two direct hypotheses developed to address the research problem. Partial Least Squares Structural Equation Modeling (PLS-SEM) and path modeling were employed to analyze the data. The results support two direct hypotheses revealing the empirical evidence on the significant relationships between microenterprises performance and finance access, and savings. The study provides an insight on how finance and savings support services, help microenterprises grow to reduce poverty and improve livings standard among Nigerian women.